FPGA-BASED MULTI-CORE PROCESSOR - Wójcik, Wojciech; Długopolski, Jacek (Computer Science, 2013)
The paper presents the results of investigations concerning the possibilities of using programmable logic devices (FPGA) for building virtual multi-core processors dedicated to the chosen application. The paper shows the designed architecture of multi-core processor specialized for performing a particular task and discuss its computation efficiency depending on the number of cores being used. The evaluation of the results are also discussed.